EXPLORING EFL LEARNERS’ PREFERENCES FOR PRAGMATIC MARKERS - Suryanovika, Citra (Jurnal Ilmiah Spectral, 2025)
This preliminary study is motivated by the role of pragmatic markers in both spoken and written communication, which reflects speaking fluency. It employs Beeching’s (2016) matched-guise methodology, utilizing online forms to engage participants from two different locations. The primary aim of this study is to investigate EFL learners’ preferences for using pragmatic markers in their utterances. To gather data, Google Forms were distributed to universities students in two different locations. A total of 39 participants completed the questionnaire, among them were 17 respondents from Central Java, 1 from Bali, 1 from West Java, and 20 from West Kalimantan. Notably, 21 participants identified English as their second language, while 18 reported it as their third language. Upon analysis, the data indicated that participants perceived utterances containing the pragmatic markers "well," "I mean," and "sort of" as embodying polite, direct, and friendly attitudes. While “like” tends to contribute to a sense of indirectness in communication, the utterances featuring "you know" and "just" had no significant impact on the directness of the statements. Future researchers should investigate the broader categories and contextual variations of these markers that were potentially overlooked in the current study.